Conducting Online Surveys in China. (December 2018) - Mei, Bing; Brown, Gavin T. L.
Using online surveys is becoming increasingly extensive and widespread. Social science research in China is no exception. However, due to contextual factors (e.g., technological constraints, social and cultural norms, and language barriers), prior successful methods may not apply. This article reports an alternative way of conducting online surveys in China, by combining local commercial online survey service providers with indigenous Web 2.0 applications. The case study demonstrates the feasibility of this approach and provides practical advice (e.g., adding incentives) on how to effectively conduct online survey in China.